THE TERM OF KELENTENG IN BAHASA INDONESIA - Ardian Cangianto (Bambuti, 2022)
This paper aims to explain the term kelenteng in Bahasa Indonesia. The temple in this paper is intended as a place of worship for the Chinese with their classification according to their respective categories. The study was conducted using literature data and observation methods. The mention of temples is a tool for referring to non-Chinese people, especially in Java, to indicate places of worship for Chinese people in general. The mention of the term temple has exceeded its limits and is generally accepted by the Chinese community as a designation for places of worship of Chinese beliefs that have various kinds.